A study on the interfacial adhesion energy between capping layer and dielectric for cu interconnects. (January 2021) - Kim, Cheol; Son, Kirak; Kim, Gahui; Kim, Sungtae; Lee, Sol-Kyu; Lee, So-Yeon; Park, Young-Bae; Joo, Young-Chang
Abstract: Recently, Cu interconnect and low-k materials have been applied to reduce the interconnect resistive-capacitive delay issue. However, as the process node size is reduced to a few nanometers, high leakage currents appear through the dielectric under high electric fields. Therefore, issues of Cu diffusion at the interface between the dielectric and the capping layer have been reported. This study investigated interfacial adhesion energy change at the film level between dielectric (low-k, tetraethyl orthosilicate (TEOS)) and capping layer (SiCN, SiN) taking into account the correlation between interfacial adhesion energy and interconnect reliability. In the capping layer/low-k interface, when low-k is applied to the top layer, it shows high interfacial adhesion energy (> 34.31 ± 3.49 J/m 2 ) due to the presence of an O-rich thin layer. But when low-k is applied to the bottom layer, due to the SiC bond, it shows low interfacial adhesion energy (< 5.60 ± 2.46 J/m 2 ). The interface between TEOS and SiN has high interfacial adhesion energy (> 32.54 ± 1.97 J/m 2 ) regardless of the stacking order and CMP process. It clearly shows that low-k dielectrics will affect the deterioration of the interfacial adhesion energy and O-rich layer will greatly improve the interfacial adhesion energy in dielectric/capping layers. Highlights: Film level interfacial adhesion energy change at the interface between the dielectric and capping layer High interfacial adhesion energy due to the formation of O-rich layer at the low-k/capping interface The lower the dielectric constant, the less effective the interfacial adhesion with the capping layer.